P, NP, and NP-Completeness : The Basics of Computational Complexity / [electronic resource] - Goldreich, Oded (Cambridge : Cambridge University Press, 2010)
The focus of this book is the P versus NP Question and the theory of NP-completeness. It also provides adequate preliminaries regarding computational problems and computational models. The P versus NP Question asks whether or not finding solutions is harder than checking the correctness of solutions. An alternative formulation asks whether or not discovering proofs is harder than verifying their correctness. It is widely believed that the answer to these equivalent formulations is positive, and this is captured by saying that P is different from NP. Although the P versus NP Question remains unresolved, the theory of NP-completeness offers evidence for the intractability of specific problems in NP by showing that they are universal for the entire class. Amazingly enough, NP-complete problems exist, and furthermore hundreds of natural computational problems arising in many different areas of mathematics and science are NP-complete.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Computational complexity; Computer algorithms; Approximation theory; Polynomials